How Does Repetitive Transcranial Magnetic Stimulation Influence the Brain in Depressive Disorders?: A Review of Neuroimaging Magnetic Resonance Imaging Studies. Issue 2 (June 2018) - Taïb, Simon; Arbus, Christophe; Sauvaget, Anne; Sporer, Marie; Schmitt, Laurent; Yrondi, Antoine
Abstract : Objective: Repetitive transcranial magnetic stimulation (rTMS) is a nonpharmacological technique used to stimulate the brain. It is a safe and proven alternative tool to treat resistant major depressive disorders (MDDs). Neuroimaging studies suggest a wide corticolimbic network is involved in MDDs. We researched observable changes in magnetic resonance imaging induced by rTMS to clarify the operational mechanism. Methods: A systematic search of the international literature was performed using PubMed and Embase, using papers published up to January 1, 2017. The following MESH terms were used: ( depression or major depressive disorder ) and ( neuroimaging or MRI ) and ( rTMS or repetitive transcranial magnetic stimulation ). We searched the databases using a previously defined strategy to identify potentially eligible studies. Results: Both structural and functional changes were observed on magnetic resonance imagings performed before and after rTMS. Various areas of the brain were impacted when rTMS was used. Although the results were very heterogeneous, a pattern that involved the anterior cingulate cortex and the prefrontal cortex emerged. These are known to be regions of interest in MDDs. However, the various parameters used in rTMS make any generalization difficult. Conclusions: Repetitive transcranial magnetic stimulation helps to treat MDDs with good efficacy. Its effect on the brain, as observed in several neuroimaging studies, seems to impact on the structural and functional features of several networks and structures involved in major depressive disorders.